2022
DOI: 10.3390/ma15176155
|View full text |Cite
|
Sign up to set email alerts
|

Steel Fiber-Reinforced Concrete: A Systematic Review of the Research Progress and Knowledge Mapping

Abstract: This study performed a scientometric-based examination of the literature on steel fiber-reinforced concrete (SFRC) to identify its key elements. Typical review papers are limited in their capacity to link distinct segments of the literature in an organized and systematic method. The most challenging aspects of current research are knowledge mapping, co-occurrence, and co-citation. The Scopus search engine was used to search for and obtain the data required to meet the goals of the study. During the data evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…According to [ 117 ], strength ratings for engineered cementitious composite (ECC) without slag were much lower than those for slag tensile ECC (5.2 MPa) [ 118 ]. Hardened concrete properties are explained in Table 4 [ 16 , 44 , 56 , 95 ]. Figure 7 represents flexural strength [ 10 , 89 , 115 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to [ 117 ], strength ratings for engineered cementitious composite (ECC) without slag were much lower than those for slag tensile ECC (5.2 MPa) [ 118 ]. Hardened concrete properties are explained in Table 4 [ 16 , 44 , 56 , 95 ]. Figure 7 represents flexural strength [ 10 , 89 , 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in the size of depressions in these occurrences might be the source of the lower water absorption measurement. The porosity of the saturated example is used to determine how much water would be absorbed [ 56 , 96 , 139 ]. Figure 14 shows the moisture content [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on fiber-reinforced concrete began in the early 20th century, with steel fiber-reinforced concrete developing the fastest. Steel fiber-reinforced concrete has been widely used in various fields, including bridges, tunnel linings, road surfaces, and precast components [7]. Previous studies have shown that, during the concrete curing process, steel fibers can effectively reduce concrete shrinkage and the number of cracks, while enhancing strength and ductility [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, when PBL shear connectors are used to connect steel-concrete composite beams, premature failure of the concrete often occurs, resulting in the inability to fully exert the shear performance of the PBL shear connectors. If steel fibers with strong tensile strength are added to concrete to form Steel Fiber-Reinforced Concrete (SFRC), the mechanical properties of concrete will be greatly improved [11][12][13][14]. The improvement of concrete performance can bring out the shear resistance of PBL shear connectors, which can significantly improve the bearing capacity of steel-concrete composite beams [15].…”
Section: Introductionmentioning
confidence: 99%